Hippocampal SIRT1 signaling mediates the ameliorative effect of treadmill exercise on anxiety- and depression-like behavior in APP/PS1 mice - Yarong Wang; Yarong Wang; Rongxing Zhang; Yumin Jiang; Jingwen Liao; Jingwen Liao; Lianwei Mu; Lianwei Mu; Min Hu; Min Hu (Frontiers in Aging Neuroscience)
ObjectiveAnxiety and depression-like symptoms occur in the early stages of Alzheimer’s disease. Hippocampal Sirtuin 1 (SIRT1) signaling mediates anxiety- and depression-like behavior. Exercise training improves anxiety and depression-like behavior in various disease models, such as the rat chronic restraint stress model, rat model of posttraumatic stress disorder, and rat model of fetal alcohol spectrum disorders. Here, we aimed to investigate whether exercise ameliorates anxiety- and depression like behaviors in APP/PS1 mice and explore the potential mechanisms.MethodsAfter eight weeks of exercise intervention, we assessed anxiety- and depression-like behaviors in Alzheimer’s disease (AD) model mice. We then measured the levels of SIRT1, peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC1α), nuclear respiratory factor 1 (NRF1), mitochondrial transcription factor A (TFAM), and mitochondrial biogenesis (CO2, ATP6, and mitochondrial content) using immunofluorescence, reverse transcription-quantitative real-time PCR, and transmission electron microscopy. Finally, we investigated the effects of pharmacological activation of SIRT1 on anxiety- and depression-like behaviors, the SIRT1/PGC-1α/NRF1/TFAM signaling axis, and mitochondrial biogenesis.ResultsWe first observed that treadmill exercise improved anxiety- and depression-like behaviors in six-month-old APP/PS1 mice and increased SIRT1 levels in the hippocampus. Pharmacological activation of hippocampal SIRT1 function also reduced anxiety and depression-like behaviors in APP/PS1 mice. Meanwhile, both treadmill exercise and pharmacological activation of hippocampal SIRT1 increased the levels of PGC1α, NRF1, TFAM, and enhanced mitochondrial biogenesis (CO2, ATP6, or mitochondrial content) in the hippocampus of APP/PS1 mice.ConclusionThese findings reveal that treadmill exercise reduces anxiety- and depression-like behaviors in six-month-old APP/PS1 mice by enhancing the SIRT1-dependent PGC-1α/NRF1/TFAM axis, promoting mitochondrial biogenesis in the hippocampus.